Copaiba oleoresin presents anti-obesogenic effect and mitigates inflammation and redox imbalance in adipose tissue - Luciana Ortega TELLES; Bianca Sulzbacher da SILVA; Angélica Macedo Borges PAULINO; Sabrina Trigueiro MENDONÇA; Valéria Dornelles Gindri SINHORIN; Milena Campelo Freitas de LIMA; Valdir Florêncio VEIGA JUNIOR; Carla Regina ANDRIGHETTI; André Ferreira do NASCIMENTO; Gisele Facholi BOMFIM; Renata Azevedo Melo LUVIZOTTO (Acta Amazonica, 2022)
ABSTRACT Obesogenic diets lead to fat accumulation and dysfunctional adipose tissue. Active compounds were described in copaiba oleoresin, which presents anti-inflammatory, antimicrobial, and antioxidant properties. However, there are no data regarding the effects of copaiba oleoresin in adipose tissue. Therefore, we tested the hypothesis that the copaiba oleoresin could prevent or minimize obesity and adipose tissue inflammation and oxidative stress in response to a high sucrose diet. Male Wistar rats were randomly assigned to receiving commercial chow (C, n = 8), commercial chow and 30% sucrose added to the drinking water (S, n = 8), or commercial chow and 30% sucrose added to the drinking water + copaiba oleoresin (S+CO, n = 8). Copaiba oleoresin was given at a dose of 200 mg kg-1 day-1 by gavage for eight weeks. C and S animals received vehicle, at equivalent volume, by gavage. At the end of the experiment, blood samples and epididymal adipose tissue were collected for biochemical, inflammatory, and oxidative stress analyses. Copaiba oleoresin supplementation prevented weight gain, adiposity, insulin resistance, and increased IL-1β levels. Additionally, copaiba oleoresin partially attenuated the increase in fasting glucose levels, lipids, and IL-6 levels, and improved the redox status in adipose tissue. Our results suggest that the use of copaiba oleoresin could be a good strategy for prevention of obesity and its complications.